ANALISIS EFEKTIVITAS DAN KONTRIBUSI PAJAK BUMI DAN BANGUNAN PERDESAAN DAN PERKOTAAN (PBB-P2) TERHADAP PENDAPATAN ASLI DAERAH (PAD) DI KABUPATEN SIKKA - Margaretha Yulianti; Maria Febrianti Doa; Maria Rasdiana Bure (Universitas Nusa Nipa Maumere, 2025)
This study aims to analyze the effectiveness of the collection of Rural and Urban Land and Building Tax (PBB-P2) and its contribution to Local Original Revenue (PAD) in Sikka Regency during the period 2020-2023. The method used is descriptive quantitative with secondary data from the financial statements of the Sikka Regency Regional Revenue Agency. The results showed that the effectiveness of PBB-P2 collection fluctuates, with an average effectiveness of 90.10% which is classified in the effective category. However, the contribution of PBB-P2 to PAD is still very low, with an average of only 4.34%, which falls into the category of very less. Factors such as the low level of taxpayer compliance, tax arrears, as well as the lack of updating tax object data and socialization are the main obstacles. Therefore, optimization in tax collection strategies, increasing public awareness, and updating tax data are needed to increase the effectiveness and contribution of PBB-P2 to the PAD of Sikka Regency.